2020
DOI: 10.4012/dmj.2019-029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biological assessments of endodontic root canal sealer containing surface pre-reacted glass-ionomer (S-PRG) filler or silica filler

Abstract: Surface pre-reacted glass-ionomer (S-PRG) filler releases several ions, such as fluoride, borate and strontium ions, to exert bioactive effects. We fabricated an endodontic root canal sealer containing S-PRG fillers (S-PRG sealer) and then evaluated the antibacterial and anti-inflammatory properties of S-PRG sealer compared with sealer containing conventional silica fillers (silica sealer). Antibacterial tests showed that S-PRG sealer significantly reduced the turbidity of Enterococcus faecalis compared with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…2016, Miyaji et al . 2020). Bacteria P. acnes, A. israelii , and fungus Candida albicans are frequently isolated and characterized from the root canal in apical periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2016, Miyaji et al . 2020). Bacteria P. acnes, A. israelii , and fungus Candida albicans are frequently isolated and characterized from the root canal in apical periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in a previous rat study demonstrated that the anti‐inflammatory effect of S‐PRG sealer implanted into subcutaneous tissue involved a decrease in CD68 cell infiltration (Miyaji et al . 2020). In the current study, the CD68 (ED1) reduction in macrophages in response to S‐PRG or Ca(OH) 2 indicated that the bacterial stimuli subsided and the inflammation resolved in the periapical area, which is of critical importance in the regulation of periapical tissue remodelling and the relief of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an endodontic root canal sealer containing an S-PRG filler (i.e., S-PRG sealer) exhibited good antibacterial and anti-inflammatory properties. Finally, the implantation of S-PRG sealer into the subcutaneous tissues of rats noticeably decreased their inflammatory responses [17].…”
mentioning
confidence: 89%
“…In addition, an endodontic root canal sealer containing an S-PRG filler (i.e., S-PRG sealer) exhibited good antibacterial and anti-inflammatory properties. Finally, the implantation of S-PRG sealer into the subcutaneous tissues of rats noticeably decreased their inflammatory responses [17].The primary objective of this study was to examine the inhibitory effects of GIC restoratives and coating materials containing S-PRG fillers on enamel demineralization to evaluate their anticaries properties. The null hypothesis was that the GIC and S-PRG fillers would not inhibit the demineralization of bovine enamel specimens incubated in a lactic acid solution with pH = 4.0.Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 8 April 2020…”
mentioning
confidence: 99%